SANITASI DAN HIGIENIE PENGOLAHAN IKAN TUNA DAN CAKALANG ASAP DITANAH TINGGI DESA GOTALAMO KABUPATEN PULAU MOROTAI - Rorano, Malka; Nur, Rinto M (Aksara Public, 2019)
Fish is one of the foodstuffthats which is quickly decomposed and damaged, therefore it is often preserved. There are several ways to preserve fish, including drying and fumigation. In general, the people of Morotai Island carry out the processes of fish fumigation traditionally. The fumigation is conducted by placing the fish above wood that is burned, so that direct contact between fish and smoke occurs. In addition, the fumigation carried out also uses simple equipment and less attention to sanitation and hygiene aspects. This can have an impact on health and environment. The current research aimed to determine the processing of smoked tuna and skipjack fish and the application of sanitation and hygiene in its processing in Tanah Tinggi, Gotalamo Village Kabupaten Pulau Morotai. Data obtained from interviews with business actors using questionnaires and direct observation of the manufacturing process smoked fish. The results of the study showed that the smoked fish business was still in the home industry scale whose processing was carried out by the business owner and assisted family members. This industry was still simple and smoked fish processing was conducted traditionally. It was established in 2008. The step in producing of smoked fish includes fish cleavage, discarded gills and stomach contents, washed, clamped with bamboo, washed again, weeded, smoked, and be lubricated with cooking oil. Furthermore, the process of producing smoked fish was not meeting sanitation and hygiene standards, both in terms of workers, equipment and the place.